National Value System Impact On The Economy Of Armenia - Khachatryan, Nonna; Sargsyan, Hrachya (Տիգրան Մեծ)
The process of accumulation and economic growth of national wealth has traditionally been linked in theory and in practice to the geographical position of the country, mineral wealth, high-quality human capital, historical events. The article attempts to break this stereotype by linking the country‘s economic progress with the national value system. To this end, philosophical interpretations of the peculiarities of the Armenian people‘s national value system are made, analyzing the nation-wide advantages and disadvantages that directly affect the economic progress of the country. In particular, the manifestations of national values that impede Armenia‘s economic progress are revealed. In this respect, philosophical interpretation is given for Armenians, doing more effectively implement their entrepreneurial skills abroad, rather than in their homeland.
Keywords: Philosophy